VIDEO ADVERTORIAL EKSOTIS KEPRI DI BATAM TELEVISI "DESTINASI WISATA PATUNG SERIBU WAJAH TANJUNGPINANG" MENGGUNAKAN METODE EPIC MODEL: - - Arif, Adi Baitul Yusri; Aji, Satria Bayu (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
The progress of society demands continuous human growth in various fields. Video is one of the media currently favored by the general public. Video advertorial is a form of advertisement that subtly persuades viewers through editorial language. Riau Islands have many unique and beautiful tourist destinations, one of which is the Thousand Faces Statue Tourism in Tanjungpinang, which is still relatively less visited by the broader public. The Thousand Faces Statue Tourism features hundreds of statues that showcase different appearances and personalities. The good and bad traits of humans can be reflected through the facial expressions carved on the statues. The stages of planning a video advertorial consist of pre-production, production, and post-production stages. The output of this design is a video advertorial of Thousand Faces Statue Tourism, which will be broadcasted on the Exotic Kepri program on Batam TV. The data collection method in this design uses a combination of qualitative and quantitative methods. Qualitative methods include observation and interviews, while quantitative methods involve surveys in the form of questionnaires. Data analysis involves the Epic Model analysis (Empathy, Persuasion, Impact, Communication) and the survey results.